2019
DOI: 10.13102/sociobiology.v66i1.3679
|View full text |Cite
|
Sign up to set email alerts
|

Are Orchid Bees (Apidae: Euglossini) Good Indicators of the State of Conservation of Neotropical Forests?

Abstract: This work discusses the criteria proposed to consider wild bees as bioindicators and specifically applied to orchid bees in neotropical forests. Some of the issues are: 1) the deficiencies of the sampling methods, which makes it difficult to accurately assess species inventories. 2) missing knowledge about the biology of many species. 3) spatial or temporal distribution of most species remains unknown, which may misslead the results of short-term studies. 4) It is not clear whether orchid bees are affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
1
1
Order By: Relevance
“…Furthermore, the mechanisms driving the declines seem to be equally affecting both rare and common species. Research is still needed to understand basic aspects of the biology of orchid bees in order to comprehend how these declines are driven (Añino et al 2019). Monitoring of orchid bees in the city of Belo Horizonte in Brazil (Nemésio et al 2015) and in central Panamá (Roubik 2001;Roubik and Ackerman 1987) showed long-term stability, despite year-to-year variation in abundance, which contrasts sharply with our data.…”
Section: Population Declinecontrasting
confidence: 99%
“…Furthermore, the mechanisms driving the declines seem to be equally affecting both rare and common species. Research is still needed to understand basic aspects of the biology of orchid bees in order to comprehend how these declines are driven (Añino et al 2019). Monitoring of orchid bees in the city of Belo Horizonte in Brazil (Nemésio et al 2015) and in central Panamá (Roubik 2001;Roubik and Ackerman 1987) showed long-term stability, despite year-to-year variation in abundance, which contrasts sharply with our data.…”
Section: Population Declinecontrasting
confidence: 99%
“…Future surveys in Belize would benefit from being conducted during other times of year, especially during the June–September wet season, as well as in several major locations we did not sample, in order to extend the range of variation in elevations, habitat classes, and quantified levels of disturbance. Combined with surveys of other insects, future studies of euglossines in Belize could contribute to determining the value of orchid bees as overall indicator species in conservation studies, which has been the subject of recent debate ( Añino, Parra & Galvez, 2019 ; Allen et al, 2019 ; Miranda et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%